Influence of pre-stretching at ambient and cryogenic temperatures on dislocation configuration, precipitation behaviour, and mechanical properties of 2195 Al-Cu-Li alloy - Fan Ye; Youxing Yu; Baoshuai Zhang; Jian Rong; Donglei He; Baoshuai Han; Xiaoguang Ma; Yuansong Zeng; Yanjin Xu; Sujun Wu (Journal of Materials Research and Technology, 2023)
A novel treatment process that involves solution treatment, cryogenic pre-stretching, and artificial aging was applied to strengthen Al-Cu-Li alloy without ductility sacrificing in this work. The influence of pre-stretching deformation at ambient (RT, 25 °C) and cryogenic (CT, −196 °C) temperatures on dislocation configuration, precipitation behaviour, and after-aging mechanical properties of AA2195 was systematically investigated. Compared with conventional RT-stretched sample, the after-aging yield strength (YS) of CT-stretched sample was increased from 618 MPa to 655 MPa with ductility of 11.6%. The increased strength resulted from the combination of strain hardening and precipitation strengthening. The activated immovable dislocations on {100}Al during CT-stretching obstructed the subsequent slip of following dislocations to grain boundaries, prevented the dislocations piling-up at grain boundaries, and facilitated the dislocation accumulation at grain interior. The increased dislocations density within grains not only provided higher strain hardening to the alloy but also promoted the nucleation of T1 phase in the matrix, which significantly increased the yield strength. Additionally, the reduction of grain boundary dislocations suppressed the precipitation of T1 at grain boundaries, which prevented the formation of precipitate-free zones (PFZs) and the stress concentration at grain boundary during deformation, enhancing the alloy ductility.